Shared Genetic Architecture and Causal Relationship Between Asthma and Cardiovascular Diseases: A Large-Scale Cross-Trait Analysis - Zhou, Yi; Liang, Zhi-Sheng; Jin, Yinzi; Ding, Jiayuan; Huang, Tao; Moore, Jason H.; Zheng, Zhi-Jie; Huang, Jie (Frontiers in Genetics, 2022)
1 Abstract Background Accumulating evidence has suggested that there is a positive association between asthma and cardiovascular diseases (CVDs), implying a common etiology between them. However, the shared genetic etiology and causality of asthma and CVDs remains unclear. Methods Based on the genome-wide association study (GWAS) summary statistics of recently published studies, our study examined the genetic correlation, shared genetic variants and causal relationship between asthma (N = 142,486) and CVDs (N = 86,995 - 521,612). Statistical methods included high-definition likelihood (HDL), cross-trait meta-analyses of large-scale GWAS, transcriptome-wide association studies (TWAS), and mendelian randomization (MR). Results First, we observed significant genetic correlation between asthma and heart failure (HF) (Rg=0.278, P=5x10-4). Through cross-trait analyses, we identified a total of 145 shared loci between asthma and HF. Fifteen novel loci were not previously reported for association with either asthma or HF. Second, we these 145 loci map to a total of 99 genes whose expressions are enriched in a broad spectrum of tissues, including seminal vesicle, tonsil, appendix, spleen, skin, lymph nodes, breast, cervix and uterus, skeletal muscle, small intestine, lung, prostate, cardiac muscle, and liver. TWAS analysis identified five significant genes shared between asthma and HF in tissues from the hemic and immune system, digestive system, integumentary system, and nervous system. GSDMA, GSDMB and ORMDL3 are statistically independent genetic effects from all shared TWAS genes between asthma and HF. Third, through MR analysis, we found that asthma is causally associated with HF (per 1 unit increase in logOR of asthma, P=1.31x10-3) while there is no evidence to support the causal effect of HF on asthma (P>0.05). Conclusions These findings provide strong evidence of genetic correlations and causal relationship between asthma and HF, suggesting a shared etiology for these two diseases.